(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
Photography is one of the major disciplines for graphic students. This course is usually conducted during the early semesters of studies and students are usually exposed to a basic level. Only after years of training and in the field studies, students are able to acquire the correct skills and techniques in photography. Therefore, early photographs produced by college students display a lack of merit and are less superior in quality. Moreover, these pictures look empty and any sublime messages, intended for the audience, are conveyed in a vague and misleading fashion. This paper defines six variables of the gestalt theory for enhancing the students’ skills and performance in photography. Gestalt theory can be used and applied to develop artwork into being more interesting and vibrant. The conceptual model is introduced and aims for educators to use it as a guide for teaching photography in their courses; so that students can upgrade their skills and performance earlier and make use of game based learning as an interactive media for learning photography.